An evaluation of the physiological uptake range of 18F-fluoro-2-deoxy-D-glucose in normal ovaries of seven dogs using positron emission tomography/computed tomography - Choi, Jinyoung; Chae, Yeon; Kang, Byeong-Teck; Lee, Sungin (Frontiers in Veterinary Science, 2024)
Introduction This study evaluated the physiological uptake range of 18F-fluoro-2-deoxy-D-glucose (18F-FDG) in normal ovaries in seven dogs using positron emission tomography/computed tomography (PET/CT). Methods The dogs were placed under general anesthesia and positioned in ventral recumbency for the PET/CT scan. The dosage of 18F-FDG ranged from 0.14–0.17 mCi/kg and was administered followed by intravenously 0.9% NaCl flushing. Exactly 60 minutes after injection of 18F-FDG, PET/CT images of each dog were obtained. The regions of interest were drawn manually, and standardized uptake values (SUV) were calculated to evaluate 18F-FDG uptake in each ovary. The maximum and mean SUVs (SUV max and SUV mean) for all the dogs ovaries were then computed. Results The range of SUV max and SUV mean of normal ovaries of dogs were 1.28–1.62 and 1.07–1.31 (mean ± standard deviation), respectively. Conclusion This is the first study to investigate normal 18F-FDG uptake baseline data of normal canine ovaries on PET/CT scan. This will help clinicians identify malignant tumors before anatomical changes in ovary through PET/CT scans.